DAMPAK PENATAAN KAWASAN SIMPANGLIMA KOTA SEMARANG TERHADAP PENDAPATAN PEDAGANG MAKANAN - Utami Putri, Erleine Rastiani; Mudakir, Y. Bagio (Diponegoro Journal of Economics, 2013)
Semarang Simpanglima region as growth poles and the central office activities will be followed by activities surrounding the growth of support activities such as the growth of trade and services. The existence of relocating street vendors located in the region resulted in a reduction in the number of traders Simpanglima especially haberdasher.The method of this study used paired t test. The type of data is primary data which obtained from 85 household samples in Simpanglima.The results of these study show value of a paired t test for the variable number of consumers in the food traders Simpanglima a decline of 45.66%. For a paired t test on a variable number of production by 48.90%. For the variable of labor in food traders after relocation has decreased by 40%. For variable turnover in the food trade after the relocation has decreased by 55.34%. And for the variable profits after a relocated food vendors has decreased by 66.74%.